Budowa geologiczna rejonu Otyń-Niedoradz (krawędź pradoliny głogowsko-barudzkiej) = Geological structure of Otyń-Niedoradz region (margin of głogowsko-barudzka proglacial stream valley) - Kraiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents geological structure of a fragment of głogowsko-barudzka proglacial stream valley in region of Otyń and Niedoradz. Authar discuss with the model of geological structure presented in Geological Map of Poland. Authar describes several levels of silts within the valley limits.
Keywords: pradolina głogowsko-barudzka; osady zastoiskowe; głogowsko-barudzka proglacial stream valley; marginal lake sediments